A Method for Quantifying the Synergistic Inhibitory Effect of Corrosion Inhibitors When Used in Combination: A 'Chromate Generating Coating'. Issue 15 (18th November 2019) - Wint, N.; Ansell, P.; Edy, J.; Williams, G.; McMurray, H. N.
Abstract : Corrosion inhibitive pigments, based on the cations Ce 4+ and Cr 3+ exchanged into smart release resins, are dispersed in a polyvinyl butyral (PVB) model coating and applied to a hot dip galvanised steel (HDG) substrate. An investigation is made into the influence of different pigment volume fractions (ø pig ) of Ce(IV) and Cr(III) based inhibitors, used both in isolation and combination, on the kinetics and mechanism of corrosion driven cathodic coating delamination. The rate of coating delamination is obtained using scanning Kelvin probe (SKP) potentiometry and time lapse photography, and the efficiency with which each inhibitor combination is able to resist cathodic coating delamination is calculated. Isobolograms, commonly utilized within the field of drug interaction, are presented as an effective method for characterising corrosion inhibitor interactions. In some cases, the sum of the efficiencies calculated for Ce(IV) and Cr(III) based pigments is shown to be greater than the sum of their individual efficiencies. It is proposed that Ce 4+, released upon electrolyte exposure, is able to oxidize the Cr 3+ species resulting in the formation of transient CrO4 −2 .